IgA nephropathy: a review of existing and emerging therapies - Sahibzadi Mahrukh Noor; Farah Abuazzam; Roy Mathew; Zhiwei Zhang; Amir Abdipour; Sayna Norouzi (Frontiers in Nephrology, 2023)
IgA nephropathy (IgAN) is the most common form of primary glomerulonephritis worldwide. Recently, there have been multiple advances in the understanding of IgAN pathophysiology and therapeutic options. Despite the advent of new treatment options, individual risk stratification of the disease course and choosing the best treatment strategy for the patient remains challenging. A multitude of clinical trials is ongoing, opening multiple opportunities for enrollment. In this brief review we discuss the current approach to the management of IgAN and highlight the ongoing clinical trials.